Ultrasound Image Storage on Raspberry Pi as a Basic Data Transmission - KHOIRUNNISA, DYAH (Jurnal Teknokes, 2024)
Ultrasonography (USG) is an examination technique as one of the diagnostic aids in primary health facilities, including community health centers. With the availability of USG services, it certainly makes it easier for the public to get faster health screening and monitoring. To minimize the disparity between the number of doctors and the number of health facilities, a telemedicine system can be utilized to make services more efficient. This study was designed to create a system that can utilize Raspberry Pi as a storage medium for USG images. To ensure that no image data is lost during storage, Raspberry can be opened on another computer so that it can ensure that the USB function can work normally. The results obtained an error of 0% image loss from the sent USG images, so that it is certain that no images are lost during transmission. It is hoped that the creation of this module can be useful as a basis for developing research on sending images on further USG.